Implementasi Digitalisasi pada BMT dalam Meningkatkan Efisiensi Layanan Keuangan Syariah: Implementation of Digitalization in BMT to Increase the Efficiency of Sharia Financial Services - Raihan Maulana; Muhammad Yazid (Litera Academica Publishing, 2025)
The rapid advancement of digital technology has significantly transformed the landscape of Islamic financial institutions, including Baitul Maal wat Tamwil (BMT), which serves as a microfinance intermediary for empowering Muslim communities. This study aims to analyze the implementation of digitalization in BMT operations to improve the efficiency and accessibility of Islamic financial services. Using a qualitative descriptive approach, data were collected through interviews, documentation, and observation of several BMTs that have adopted digital platforms in their financial management systems. The findings indicate that digitalization enhances operational efficiency by streamlining transaction processes, improving financial reporting accuracy, and expanding service coverage through mobile and online applications. However, challenges such as limited digital literacy, infrastructure constraints, and data security concerns remain obstacles to optimal implementation. The study concludes that successful digital transformation in BMT requires not only technological adoption but also human resource development and regulatory support from related institutions. The results of this research contribute to the development of Islamic microfinance management theory and provide practical insights for policymakers and BMT practitioners in promoting inclusive and efficient Sharia-based financial services.